Impact Of Psychological Factors On Language Assessment In Efl Classrooms: Teachers’ Beliefs And Pracises - Bara , Nesma (Eddissi Languages Journal, 2024)
The paradigm shift in educational assessment has seen assessment and student learning as intertwined and assessment as a tool for facilitating student progress. However, there are many variables that could impact language assessment, such as psychological elements such as motivation, attitude, anxiety, and self-regulation ability. These factors should be considered or overcome when assessing EFL students' language learning tests. This study was designed to investigate EFL teachers' preferences for common assessment methods in the EFL classroom, their Assessment for Learning (AFL) practises, and whether they differed in their AFL practises according to variables such as cultural and psychological factors. A meta-literature analysis was conducted to identify possible solutions and strategies to improve language assessment and comprehension and overcome these psychological barriers in the EFL context. The findings revealed that most EFL teachers, especially in the Algerian context, rely on conventional methods of assessment rather than formative assessment processes. Effectively practising AFL requires instructors to reassess their assessment methods and create AFL strategies and feedback processes. In addition, the study revealed a significant relationship between psychological factors and students' academic performance; consequently, teachers require assessment literacy and a variety of tools to comprehend how their past views influence their teaching strategies and evaluate them in light of the new evaluation paradigm. Students may perform better on academic exams if they receive comprehensive psychological assistance in various dimensions.